Die gesamtwirtschaftlichen Wirkungen der EU-Strukturpolitik in den Konvergenzregionen: Methodische Anmerkungen und empirische Ergebnisse für die Förderperiode 2007–2013 - Bradley, John; Bradley, John; Untiedt, Gerhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
The reform of the European structural policy in the late eighties confronted the European Commission and the national policy-makers with new tasks. In contrast to many other political interventions the measures of the European Structural Funds go out explicitly over short-term stabilisation and are supposed primarily to contribute to improve the supply-side conditions in the supported national economies. The promotion scheme has the target to improve of the production conditions and to contribute for the convergence of the incomes within Europe. For the analysis of the effects are applicable a multiplicity of methods, which differ according to the economical range of the effects. In this contribution we deal with some methodical aspects in particular the overall economic effects and for the Structural Fund period 2007 to 2013. We present some selected results for the recipient countries, which come from the HERMIN models. Altogether significantly positive effects show up both for the growth of the national product and employment, whereby there are significant differences across the recipient countries, which can be traced backt to the different structural conditions within these economies.